Student's perspectives on taking courses online, blended, or a combination - Schifter, C.; Ifenthaler, Dirk; White, D. (2015)
Online education has a relatively short history in the grand history of education. With options for online delivery modes developed over the last two decades, understanding student motivations for choosing one option over another will be helpful to any institution of higher education planning new offerings. This reflective paper presents the beginning aspects of a study at one university in the United States, using a prior study from Australia as a guide.